Early exposure to and subsequent beef cattle performance with saline water - Lopez, Agustin; Arroquy, Jose Ignacio; Distel, Roberto Alejandro (2018)
Two experiments were conducted to evaluate the impact of early life exposure to high salt water on later cattle performance with saline water. In Exp. 1, 24 cow/calf pairs were randomly assigned to one of two treatments: exposure to high salt water [HSW; 7478 mg/kg of total dissolved solids (TDS)] or to low salt water (LSW; 512 mg/kg TDS) when calves were 2 to 6 mo. old. Then all calves drank low salt water for 6 mo, and subsequently high salt water for 30 d. During the last period HSW tended to eat 10% less DM (DMI; P=0.07) and drank 22% less water than LSW (WI; P<0.01). Total tract DM digestibility (TTDMD; P=0.92), blood parameters (hemoglobin and hematocrit; P>0.13), plasma glucose (P=0.18), serum minerals (P>0.08) and weight gain (ADG; P=0.85) were not affected by treatment. In Exp. 2, 24 pregnant heifers in the last month of gestation were randomly assigned to either HSW (10827 mg/kg TDS) or LSW. The exposure period ended when calves were 3 month old. Then all calves drank low salt water for 95 d, and subsequently high salt water for 30 d. During the last period no significant differences between treatments were observed for DMI (P=0.43), WI (P=0.61), TTDMD (P=0.92), blood parameters (P>0.42), plasma rennin activity (PRA; P=0.35), and ADG (P=0.16). However, HSW drank less (P<0.01) high salt water than LSW during the first two hours of drinking water restoration after a water deprivation period of 20 h. Overall, in the conditions of our study we did not find evidence that early exposure to saline water induces tolerance and improves later performance of beef cattle with salty water. However, reduced water intake (Exp. 1) and increased thirst threshold (Exp. 2) of animals early exposed to saline water need further consideration.